Biosynthesis of D-alanyl-lipoteichoic acid by Lactobacillus casei: interchain transacylation of D-alanyl ester residues. - Childs, W C (1985)
Lipoteichoic acid (LTA) from Lactobacillus casei contains poly(glycerophosphate) substituted with D-alanyl ester residues. The distribution of these residues in the in vitro-synthesized polymer is uniform. Esterification of LTA with D-alanine may occur in one of two modes: (i) addition at random or (ii) addition at a defined locus in the poly(glycerophosphate) chain followed by redistribution of the ester residues. A time-dependent transacylation of these residues from D-[14C]alanyl-lipophilic LTA to hydrophilic acceptor was observed. The hydrophilic acceptor was characterized as D-alanyl-hydrophilic LTA. This transacylation requires neither ATP nor the D-alanine incorporation system, i.e., the D-alanine activating enzyme and D-alanine:membrane acceptor ligase. No evidence for an enzyme-catalyzed transacylation reaction was observed. We propose that this process of transacylation may be responsible for the redistribution of D-alanyl residues after esterification to the poly(glycerophosphate). As a result, it is difficult to distinguish between these proposed modes of addition.